Social psychology - Hogg, Michael A (Sage, 2003)
Covering the entire scope of mainstream social psychology, this collection contains benchmark readings with an emphasis on recent key publications to complement older classic works. The readings are mainly empirical articles that not only cover the significant ideas and key debates in the field, but also show how social psychological knowledge is obtained through research. In addition to the 80 key original articles included in the collection, the set opens with an introductory editorial essay by Michael A. Hogg setting out the rationale behind the selections, and providing an illuminating discussion of the development of social psychology and its theoretical foundations.
Sage Benchmarks in psychology
Keywords: sociologie; psychologie, klinická psychologie